Sistem Prediksi Persediaan Barang Menggunakan Metode Regresi Linier Berbasis Website - Bastian Nursyahputra, Andhika; Dwi Indriyanti, Aries; Faizah, Arbiati (Inovate, 2020)
The prediction process is important for the company in the formulation of the company's strategy in the future. Therefore, a precise prediction method is needed by the company to be able to maximize the estimation of future sales. The Double Exponential Smoothing method is a popular method used in privacy because it has good performance. This method has parameter values and has a large influence on the results of predictions. This method uses data compilation that shows trends. Exponential smoothing in the presence of a trend such as a simple transmitter such as two components must be updated every period - its level and trend. Level is an estimate that is smoothed from the data value at the end of each period. A trend is a smoothed estimate of average growth. The purpose of this design produces a prediction method that is appropriate and applicable in the company to facilitate sales activities in the company. With the right prediction method, it is expected that the company can make efficient all the resources needed by the company. Keywords: Exponential Smoothing, Multiple Exponential Smoothing, level.